Survey of ICT and Education in Africa : Egypt Country Report - Hamdy, Amr (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Egypt faces significant challenges in harnessing its education system to promote its development plans. The government has articulated a vision of an information society in which widespread access to technology can nurture human capital, improve government services, promote Egyptian culture, and support economic growth, and the ICT sector has been targeted as a vehicle for this growth and social development. A national ICT policy has been adopted and is managed by the Ministry of Communication and Information Technology, of which education is one priority. The Egyptian education initiative, launched by the first lady, is a prominent result.